O-110 A randomised, controlled, assessor-blind trial assessing clinical outcomes of individualised dosing with follitropin delta in Asian IVF/ICSI patients. (6th August 2021) - Qiao, J; Zhang, Y; Liang, X; Ho, T; Huang, H Y; Kim, S H; Goethberg, M; Mannaerts, B; Arce, J C; ,
Abstract: Study question: To evaluate the efficacy and safety of individualised dosing with follitropin delta versus conventional dosing with follitropin alfa in an Asian population undergoing ovarian stimulation. Summary answer: Individualised dosing with follitropin delta results in significantly higher live birth rate and fewer early OHSS and/or preventive interventions compared to conventional follitropin alfa dosing. What is known already: Previous randomised controlled trials conducted in Europe, North- and South America mainly including Caucasian IVF/ICSI patients as well as in Japan have demonstrated that ovarian stimulation with the individualised follitropin delta dosing regimen based on serum AMH level and body weight modulated the ovarian response and reduced the risk of OHSS without compromising pregnancy and live birth rates. Study design, size, duration: Randomised, controlled, assessor-blind trial conducted in 1, 009 Asian patients from mainland China, South Korea, Vietnam and Taiwan, undergoing their first IVF/ICSI cycle. Randomisation was stratified by age (<35, 35-37, 38-40 years). The primary endpoint was ongoing pregnancy assessed 10-11 weeks after transfer (non-inferiority limit -10.0%; analysis adjusted for age strata). Patients <35 years underwent single embryo transfer if a good-quality embryo was available, otherwise double embryo transfer. Patients ≥35 years underwent double embryo transfer. Participants/materials, setting, methods: Follitropin delta (Rekovelle, Ferring Pharmaceuticals) daily treatment consisted of a fixed dose individualised according to each patient's initial AMH level (<15 pmol/L: 12 μg; ≥15 pmol/L: 0.19 to 0.10 μg/kg; min-max 6-12 μg) and body weight. Follitropin alfa (Gonal-f, Merck Serono) dose was 150 IU/day for the first five days with subsequent potential dose adjustments according to individual response. A GnRH antagonist protocol was applied. OHSS was classified based on Golan's system. Main results and the role of chance: The ongoing pregnancy rate was 31.3% with follitropin delta and 25.7% with follitropin alfa (adjusted difference 5.4% [95% CI: -0.2%; 11.0%]). The live birth rate was significantly higher at 31.3% with follitropin delta compared to 24.7% with follitropin alfa (adjusted difference 6.4% [95% CI: 0.9%; 11.9%]; p < 0.05). Live birth rates per age stratum were as follows for follitropin delta and follitropin alfa; <35 years: 31.0% versus 25.0%, 3537 years: 35.3% versus 26.7%, 38-40 years: 20.0% versus 14.3%. Early OHSS risk, evaluated as the incidence of early OHSS and/or preventive interventions, was significantly (p < 0.01) reduced from 9.6% with follitropin alfa to 5.0% with follitropin delta. The number of oocytes was 10.0±6.1 with follitropin delta and 12.4±7.3 with follitropin alfa. Individualised follitropin delta dosing compared to conventional follitropin alfa dosing resulted in 2 more oocytes (9.6±5.3 versus 7.6±3.5) in potential low responders (AMH <15 pmol/L) and 3 fewer oocytes (10.1±6.3 versus 13.8±7.5) in potential high responders (AMH ≥15 pmol/L). Among patients with AMH ≥15 pmol/L, excessive response occurred less frequently with individualised than conventional dosing (≥15 oocytes: 20.2% versus 39.1%; ≥20 oocytes: 6.7% versus 18.5%). Total gonadotropin dose was reduced from 109.9±32.9 μg with follitropin alfa to 77.5±24.4 μg with follitropin delta. Limitations, reasons for caution: The trial only covered the clinical outcome of one treatment cycle with fresh cleavage-stage embryo transfers. Wider implications of the findings: The present trial implies that in addition to reducing the early OHSS risk, individualised dosing has the potential to improve the take-home baby rate in fresh cycles across all ages and with a lower gonadotropin consumption. The benefits in outcomes appear to be explained by the modulation of ovarian response. Trial registration number: NCT03296527